2011
DOI: 10.1093/cercor/bhr355
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Aberrations in Prepubertal Estrogen-Naive Girls with Monosomic Turner Syndrome

Abstract: Turner syndrome (TS) offers a unique opportunity to investigate associations among genes, the brain, and cognitive phenotypes. In this study, we used 3 complementary analyses of diffusion tensor imaging (DTI) data (whole brain, region of interest, and fiber tractography) and a whole brain volumetric imaging technique to investigate white matter (WM) structure in prepubertal, nonmosaic, estrogen-naive girls with TS compared with age and sex matched typically developing controls. The TS group demonstrated signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 50 publications
2
18
0
2
Order By: Relevance
“…Holzapfel (2006) found lower FA in the bilateral internal capsule as well as in the left parieto‐occipital region, extending along the superior longitudinal fasciculus. Yamagata et al (2012) found widespread reductions in FA in girls with TS in a number of tracts connecting regions implicated in the cognitive deficits characteristic of TS. Turner syndrome (TS) is marked by widespread deficits in white matter pathways, especially in anterior–posterior tracts, so it is not surprising that functional connectivity is altered as well.…”
Section: Structural and Functional Connectivity In Atypical Brain Devmentioning
confidence: 87%
“…Holzapfel (2006) found lower FA in the bilateral internal capsule as well as in the left parieto‐occipital region, extending along the superior longitudinal fasciculus. Yamagata et al (2012) found widespread reductions in FA in girls with TS in a number of tracts connecting regions implicated in the cognitive deficits characteristic of TS. Turner syndrome (TS) is marked by widespread deficits in white matter pathways, especially in anterior–posterior tracts, so it is not surprising that functional connectivity is altered as well.…”
Section: Structural and Functional Connectivity In Atypical Brain Devmentioning
confidence: 87%
“…The structure of the parietal lobe [1618] and its connectivity with other cortical regions (notably the frontal cortex) [19, 20] appear to differ between individuals with TS and controls. In addition, task-based [2123] and resting-state [24] functional connectivity measures between the frontal and parietal cortex are reduced in girls with TS.…”
Section: Brain Phenotype In Ts Nf1 and Ns: Clinical And Animal Modelmentioning
confidence: 99%
“…Holzapfel (2006) found lower FA in the bilateral internal capsule as well as in the left parieto‐occipital region, extending along the superior longitudinal fasciculus. Yamagata et al (2012) found widespread reductions in FA in girls with TS in a number of tracts connecting regions implicated in the cognitive deficits characteristic of TS. Turner syndrome (TS) is marked by widespread deficits in white matter pathways, especially in anterior–posterior tracts, so it is not surprising that functional connectivity is altered as well.…”
Section: Structural and Functional Connectivity In Atypical Brain Devmentioning
confidence: 99%